Methanization potential of anaerobic biodigestion of solid food waste - Laís R. G. de Oliveira; Derovil A. dos Santos Filho; Kaline C. Vasconcelos; Talita V. de Lucena; José F. T. Jucá; André F. de M. S. Santos (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Anaerobic biodigestion of solid and semi-solid wastes has been widely used for the treatment of these residues and methane production; however, during the process (more specifically in the acidogenic phase), there is a tendency of pH reduction, an unfavorable condition to methanogenic bacteria. Thus, the present work aims to evaluate the methanization potential of an agroindustrial anaerobic granular sludge (AIS) from UASB (Upflow Anaerobic Sludge Blanket) reactor, individually and biodigested with food waste (FW) from the University Restaurant of the Federal University of Pernambuco with buffering agent (AIS + FW + b) and without it (AIS + FW). After the laboratory tests, the AIS + FW + b configuration obtained a cumulative methane production approximately six times greater than that of AIS + FW, and approximately twice that of the inoculum alone (AIS).